Preparation method of rice straw fiber rope

By softening, wiping, twisting and impregnating the rice straw, high-strength and high-strength spiral structure fiber ropes were prepared, which solved the environmental pollution problems of traditional plastic bundling ropes and the low utilization efficiency of rice straws, and achieved the development of environmentally friendly, low-cost and high-efficiency fiber bundling materials.

CN119711226AActive Publication Date: 2025-03-28AGRICULTURAL EQUIPMENT INSTITUTE OF HUNAN
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510004977.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-28
Estimated Expiration
2045-01-02

Smart Images

  • Figure CN119711226A_ABST
    Figure CN119711226A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a rice straw fiber rope, and belongs to the technical field of fibers. Comprising the following steps: S1, a rice straw softening regulation and control process: treating rice straws through a softening solvent, and regulating and controlling cell wall chemical components and physical structures of the rice straws; s2, separation and preparation of rice straw long fibers: a winding bar coater is adopted to perform repeated reciprocating rolling and filament separation treatment on the softened rice straw in the radial direction of the straw, and the rice straw long fibers with the diameter being 50-800 microns and the length being 100-500 mm are obtained through separation; s3, a directional spiral structure twisting process: performing directional twisting treatment on the rice straw long fibers through a twisting device to obtain a high-strength and high-toughness rice straw long fiber rope with a spiral structure; and S4, post-treatment and curing are conducted, specifically, the rice straw fiber rope is subjected to dipping treatment, and the spiral structure and high-strength and high-toughness fibers are endowed with multiple properties such as bacteriostasis, water resistance and weather resistance. The rice straw fiber rope which is of a spiral structure, high in strength and toughness and capable of being naturally degraded can be obtained and can be applied to multiple fields of industry, agriculture, medical treatment, food and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of biomass material preparation technology and high-value utilization of agricultural waste, in particular to a method for preparing a rice straw fiber rope. Background Art

[0002] As a structural material widely used in industry, agriculture and daily life, the main function of strapping rope is to tightly fix items for easy transportation and storage. At present, most mainstream high-strength plastic strapping ropes are processed from petrochemical raw materials such as polypropylene and polyester. However, traditional petrochemical-based plastic strapping ropes consume a lot of energy and have a high carbon footprint during the production process. After strapping, they need to be accurately recycled to prevent livestock from accidentally eating them. In addition, at the end of their life, they will degrade into plastic fragments and particles, which will cause ecological pollution and harm the ecological environment after entering the environment. Therefore, the development of a new, environmentally friendly strapping rope material with super strong and super toughness has become a practical production problem that needs to be solved urgently.

[0003] Rice straw is the main residue after rice harvest. Improper treatment can easily lead to resource waste, environmental pollution and farmland soil degradation. At present, rice straw is mainly used in the extraction of cellulose and hemicellulose components, pulping and papermaking, building materials and biofuel conversion. However, there are no reports on processing rice straw into high-strength and high-tenacity fiber materials, especially as special-purpose materials such as baling ropes.

[0004] There are natural pore structures of varying sizes in rice straw, which can be deformed under the action of external forces. By reducing the fiber distance in the rice straw cell wall and increasing the fiber contact area, the mutual friction between fibers and stress dispersion transfer are enhanced. In addition, the cell wall of rice straw is composed of rigid lignin, semi-rigid cellulose and hemicellulose components. Through rigid-flexible regulation, the deformation properties of rice can be enhanced. Therefore, by changing the micro-nano structure and chemical composition of rice straw, regulating the flexibility, plasticity, friction and adaptability of rice straw to external forces, changing the stress transfer and fracture failure of rice straw, and improving the mechanical strength and fracture failure deformation.

[0005] The present invention proposes a novel method for preparing a spiral structure, high-strength and high-tenacity fiber bundling rope using rice straw, which has important practical significance and broad application prospects. This not only helps to solve the problem of rice straw waste disposal, but also can provide a new, low-cost, high-efficiency fiber bundling material for related industries, promote the resource utilization of agricultural waste, and has high economic value and social benefits. Summary of the invention

[0006] The present invention aims to provide a rice straw fiber rope and a preparation method thereof. The core of the present invention is: S1. Rice straw softening process: rice straw is treated with a softening solvent to regulate the chemical composition and physical structure of the cell wall of rice straw; the softening solvent comprises one or more of water, organic solvent, low eutectic solvent and Lewis base, the solid-liquid mass ratio of rice straw to softening solvent is 1:5~1:100, the pre-impregnation time is 5~500 min at room temperature (5~40 ℃), and then the mixture is transferred to a high-temperature reactor, the treatment temperature is adjusted to 60~300 ℃, the pressure value is adjusted to 0.02~8.6 MPa, and the treatment time is 5~300 min, and after natural cooling, wash with water until neutral to obtain softened rice straw; the water includes tap water, distilled water or deionized water; the organic solvent includes one or more combinations of methanol, ethanol, acetone, γ-valerolactone, formic acid, acetic acid, p-toluenesulfonic acid, and oxalic acid; the low eutectic solvent includes one or more combinations of choline chloride system and trioctylmethylammonium chloride salt system; the Lewis base includes one or more combinations of ammonia water, sodium hydroxide, potassium hydroxide, aluminum chloride hexahydrate, and sodium carbonate; S2. Separation and preparation of long fibers from rice straw: The softened rice straw obtained in S1 was subjected to reciprocating rolling and splitting treatment along the radial direction of the straw using a wire rod coater to separate the long fibers from the rice straw, and the long fibers were placed in a constant temperature and humidity chamber to maintain a moisture content of 20% to 200%; S3. Directed spiral structure twisting process: The rice straw long fibers separated in S2 are subjected to directional twisting by a twisting device to obtain a rice straw long fiber rope with a spiral structure, high strength and high tenacity; the twisting process is set to a twist of 5-20 t / cm, a twist angle of 10°-80°, and a twist coefficient of 250-400. The diameter of the twisted rice straw fiber rope is 0.5-30 mm, the density is 0.9-1.5 g / cm³, the internal fiber orientation angle is 5°-88°, the tensile strength is 50-600 MPa, and the tensile fracture deformation rate is 10%-100%; S4. Post-treatment and curing: The rice straw fiber rope is impregnated with an impregnation solution including polyvinyl alcohol, soy protein isolate, chitosan, and alkali lignin polymer solution. The concentration of the polymer in deionized water is controlled at 0.1 wt%~10 wt%, the impregnation temperature is controlled at 40~60 ℃, and the impregnation time is controlled at 1~6 h to ensure that the rice straw fiber rope is in full contact with the polymer. After the impregnation treatment, the fiber rope is taken out and naturally air-dried at 20~40 ℃ or heat-dried in an oven at 40~60 ℃ for 2~48 h.

[0007] In a further technical scheme, in step S1, it specifically includes: using subcritical hydrothermal softening treatment, using water as the softening solvent, the solid-liquid mass ratio of rice straw to the softening solvent is 1:5, pre-impregnation time is 500 min at room temperature (5~40 ℃), transferred to a high-temperature reactor, adjusting the treatment temperature to 160 ℃, treatment time 90 min, the softened rice straw is measured to have a crystallinity of 28%~40%, a cellulose content of 55%~60%, a hemicellulose content of 10%~15%, a lignin content of 10%~18%, an ash content of 4%~5%, a wall thickness of 15~20 μm, a wall layer gap of 1.5~3.0 μm, and a wall layer porosity of 55%~65%.

[0008] In a further technical scheme, in step S1, it specifically includes: using subcritical hydrothermal to soften the straw with a solid-liquid ratio of 1:10, pre-impregnating for 300 min at room temperature (5~40 ℃), transferring to a high-temperature reactor, adjusting the treatment temperature to 200 ℃, and treating for 30 min. The softened rice straw is measured to have a crystallinity of 30%~45%, a cellulose content of 55%~60%, a hemicellulose content of 8%~12%, a lignin content of 10%~13%, an ash content of 5%~7%, a wall thickness of 13~18 μm, a wall layer gap of 2.1~3.5 μm, and a wall layer porosity of 60%~65%.

[0009] In a further technical scheme, in step S1, it specifically includes: using formic acid-methanol system for softening treatment, with a solid-liquid ratio of 1:10, pre-impregnating for 60 min at room temperature (5~40 ℃), transferring to a high-temperature reactor, adjusting the treatment temperature to 100 ℃, the treatment time is 40 min, washing to neutrality, and measuring the softened rice straw to have a crystallinity of 40%~48%, a cellulose content of 55%~65%, a hemicellulose content of 2%~5%, a lignin content of 5%~10%, an ash content of 4%~5%, a wall thickness of 12~15 μm, a wall layer gap of 2.5~3.8 μm, and a wall layer porosity of 60%~65%.

[0010] In a further technical scheme, in step S1, it specifically includes: using choline chloride-ethylenediamine low eutectic solvent for softening treatment, with a solid-liquid ratio of 1:30, pre-impregnating for 60 min at room temperature (5~40°C), transferring to a high-temperature reactor, adjusting the treatment temperature to 120°C, the treatment time is 60 min, washing with water to neutrality, and measuring the softened rice straw to have a crystallinity of 45%~50%, a cellulose content of 60%~65%, a hemicellulose content of 5%~8%, a lignin content of 4%~8%, an ash content of 2%~4%, a wall thickness of 15~18 μm, a wall layer gap of 2.0~3.5 μm, and a wall layer porosity of 55%~60%.

[0011] In a further technical scheme, in step S1, it specifically includes: using trioctyl methyl ammonium chloride salt-ammonium chloride low eutectic solvent and peracid for softening and delignification treatment, the solid-liquid ratio is 1:20, pre-impregnating with trioctyl methyl ammonium chloride salt-ammonium chloride low eutectic solvent for 60 min at room temperature (5~40 ℃), transferring to a high-temperature reactor, adjusting the treatment temperature to 80 ℃, the treatment time is 180 min, washing with water to neutrality, and then using peracid to assist delignification, washing with water to neutrality. The softened rice straw is measured to have a crystallinity of 45%~55%, a cellulose content of 75%~85%, a hemicellulose content of 2%~5%, a lignin content of 1%~6%, an ash content of 1%~4%, a wall thickness of 12~15 μm, a wall layer gap of 3.0~4.5 μm, and a wall layer porosity of 65%~70%.

[0012] In a further technical scheme, in step S1, it specifically includes: using sodium hydroxide, sodium sulfite and peracid for softening and delignification treatment, the solid-liquid ratio is 1:20, pre-impregnating with sodium hydroxide solution at room temperature of 5~40 ℃ for 120 min, transferring to a high-temperature reactor, adjusting the treatment temperature to 80 ℃, the treatment time is 60 min, washing with water to neutrality, and then using peracetic acid for full delignification treatment. After washing with water to neutrality, the softened rice straw is measured to have a crystallinity of 45%~60%, a cellulose content of 90%~95%, a hemicellulose content of 1%~4%, a lignin content of 0%~2%, an ash content of 0~1%, a wall thickness of 10~12 μm, a wall layer gap of 2.5~4.5 μm, and a wall layer porosity of 70%~75%.

[0013] Compared with the prior art, the method for preparing a rice straw fiber rope of the present invention has the following beneficial effects: 1. The present invention uses a softening agent to treat rice straw, regulates the lignin content in the cell wall of the rice straw, reduces the rigidity of the rice straw, and makes the rice straw easier to bend and twist when twisted, thereby forming a spiral structure; at the same time, by regulating the cellulose content in the rice straw, the hydrogen bond strength between the rice straw fibers can be enhanced, and the fibers can be tightly bound during the later twisting; 2. The present invention rolls the softened rice straw back and forth along the radial direction of the wire rod coater, utilizes the contact and friction shear stress between the coil and the rice straw, promotes the effective separation of the straw deformation and the long fiber, and controls the diameter of the separated fiber by adjusting the coil diameter and coil gap of the wire rod coater; 3. The present invention adopts a twisting process to directional assemble the separated long fibers of rice straw. The spiral structure is formed by mechanical effects such as physical interweaving, winding and friction, which enhances the degree of fiber interlocking, makes stress transmission more uniform, and enables the spiral fiber to withstand greater external stress. At the same time, when subjected to stretching, the de-helicalization and fiber slippage help to delay the breakage, thereby simply and efficiently preparing high-strength fiber ropes. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative labor. Figure 1 This is a flow chart of a method for preparing a rice straw fiber rope according to the present invention; Figure 2 The actual pictures and scanning electron microscope pictures of rice straw obtained by different softening processes of the present invention (Figures a and e are the actual pictures and scanning electron microscope pictures of the original rice straw; Figures b and f are the actual pictures and scanning electron microscope pictures of the rice straw after hydrothermal treatment of the first embodiment; Figures c and g are the actual pictures and scanning electron microscope pictures of the partially delignified rice straw of the third embodiment; Figures d and g are the actual pictures and scanning electron microscope pictures of the fully delignified rice straw of the sixth embodiment); Figure 3 The spiral structure, high-strength and high-tenacity rice straw fiber rope of the first embodiment of the present invention; Figure 4 XRD diffraction patterns of rice straws using different softening processes of the present invention (a is the original rice straw, b is the hydrothermal rice straw of the first embodiment, c is the partially delignified rice straw of the third embodiment, and d is the fully delignified rice straw of the sixth embodiment); Figure 5 Infrared spectra of rice straws using different softening processes of the present invention (a is the original rice straw, b is the hydrothermal rice straw of the first embodiment, c is the partially delignified rice straw of the third embodiment, and d is the fully delignified rice straw of the sixth embodiment). Specific implementation methods

[0015] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] like Figure 1As shown, a method for preparing a rice straw fiber rope according to the first embodiment 1 of the present invention comprises the following steps: S1 Rice straw softening process: subcritical hydrothermal softening treatment was used, water was used as the softening solvent, the solid-liquid mass ratio of rice straw to softening solvent was 1:5, the pre-impregnation time was 500 min at room temperature of 5-40 ℃, and then the straw was transferred to a high-temperature reactor, the treatment temperature was adjusted to 160 ℃, and the treatment time was 90 min. The softened rice straw was measured to have a crystallinity of 28%-40%, a cellulose content of 55%-60%, a hemicellulose content of 10%-15%, a lignin content of 10%-18%, an ash content of 4%-5%, a wall thickness of 15-20 μm, a wall interlayer gap of 1.5-3.0 μm, and a wall porosity of 55%-65%; S2. The rice straw softened in step S1 is treated with a wire rod coater, and is subjected to reciprocating rolling and separation processing along its radial direction, and rice straw long fibers with a diameter of 100-2000 μm and a length of 100-500 mm are separated according to the gap depth and the number of rolling times, and are placed in a constant temperature and humidity chamber to maintain a moisture content of 20%-200%; S3 The rice straw long fibers prepared in S2 are subjected to directional twisting treatment by a manual twisting device, with a twist of 5 t / cm and a twist angle of 10°. The rice straw cellulose rope obtained after twisting has a diameter of 0.5-5 mm, a density of 1.2-1.5 g / cm³, a twist coefficient of 280-320, and a fiber orientation angle of 20°-25°; S4 The twisted rice straw fiber rope was impregnated with 0.1 wt% polyvinyl alcohol / soy protein isolate / chitosan / alkali lignin solution. The impregnation temperature was controlled to be 40 ℃ for 6 h, and then it was taken out and dried in a 40 ℃ oven for 12 h. Figure 2 and 3 As shown, after softening, rice straw can be split into long fibers, which can be twisted in a directional manner to form long ropes with good winding and bending properties.

[0017] Second embodiment 2: S1 Rice straw softening process: Subcritical hydrothermal softening treatment was used with a solid-liquid ratio of 1:10. The pre-impregnation time was 300 min at room temperature of 5-40 °C, and then the mixture was transferred to a high-temperature reactor. The treatment temperature was adjusted to 200 °C and the treatment time was 30 min. The softened rice straw had a crystallinity of 30%-45%, a cellulose content of 55%-60%, a hemicellulose content of 8%-12%, a lignin content of 10%-13%, an ash content of 5%-7%, a wall thickness of 13-18 μm, a wall interlayer gap of 2.1-3.5 μm, and a wall porosity of 60%-65%. S2. The rice straw softened in step S1 is treated with a wire rod coater, and is subjected to reciprocating rolling and separation processing along its radial direction, and rice straw long fibers with a diameter of 100-2000 μm and a length of 100-500 mm are separated according to the gap depth and the number of rolling times, and are placed in a constant temperature and humidity chamber to maintain a moisture content of 20%-200%; S3 The rice straw long fibers prepared in S2 are subjected to directional twisting treatment by a manual twisting device, with a twist of 10 t / cm and a twist angle of 20°. The diameter of the rice straw cellulose rope obtained after twisting is 1-8 mm, the density is 1.4-1.6 g / cm³, the twist coefficient is 270-320, and the fiber orientation angle is 30°-60°; S4 The twisted rice straw fiber rope was impregnated with 1 wt% polyvinyl alcohol / soy protein isolate / chitosan / alkali lignin solution. The impregnation temperature was controlled at 50 °C for 3 h, and then it was taken out and dried in an oven at 60 °C for 6 h.

[0018] Third embodiment 3: S1 Rice straw softening process: formic acid-methanol system was used for softening treatment, with a solid-liquid ratio of 1:10, pre-impregnation time of 60 min at room temperature of 5-40 °C, transferred to a high-temperature reactor, and the treatment temperature was adjusted to 100 °C, the treatment time was 40 min, and washed with water until neutral. The softened rice straw was measured to have a crystallinity of 40%-48%, a cellulose content of 55%-65%, a hemicellulose content of 2%-5%, a lignin content of 5%-10%, an ash content of 4%-5%, a wall thickness of 12-15 μm, a wall interlayer gap of 2.5-3.8 μm, and a wall porosity of 60%-65%; S2. The rice straw softened in step S1 is treated with a wire rod coater, and is subjected to reciprocating rolling and separation processing along its radial direction, and rice straw long fibers with a diameter of 100-2000 μm and a length of 100-500 mm are separated according to the gap depth and the number of rolling times, and are placed in a constant temperature and humidity chamber to maintain a moisture content of 20%-200%; S3 The rice straw long fibers prepared in S2 are subjected to directional twisting treatment by a manual twisting device, with a twist of 10 t / cm and a twist angle of 20°. The rice straw cellulose rope obtained after twisting has a diameter of 1-8 mm, a density of 1.2-1.4 g / cm³, a twist coefficient of 300-350, and a fiber orientation angle of 40°-65°; S4 The twisted rice straw fiber rope was impregnated with 5 wt% polyvinyl alcohol / soy protein isolate / chitosan / alkali lignin solution. The impregnation temperature was controlled at 60 °C for 1 h, and then it was taken out and dried in an oven at 60 °C for 8 h.

[0019] Fourth embodiment 4: S1 Rice straw softening process: choline chloride-ethylenediamine low eutectic solvent was used for softening treatment, with a solid-liquid ratio of 1:30, pre-impregnation time of 60 min at room temperature (5-40 °C), transfer to a high-temperature reactor, adjust the treatment temperature to 120 °C, treatment time of 60 min, wash to neutrality, and the softened rice straw was measured to have a crystallinity of 45%-50%, a cellulose content of 60%-65%, a hemicellulose content of 5%-8%, a lignin content of 4%-8%, an ash content of 2%-4%, a wall thickness of 15-18 μm, a wall layer gap of 2.0-3.5 μm, and a wall layer porosity of 55%-60%; S2. The rice straw softened in step S1 is treated with a wire rod coater, and is subjected to reciprocating rolling and separation processing along its radial direction, and rice straw long fibers with a diameter of 100-2000 μm and a length of 100-500 mm are separated according to the gap depth and the number of rolling times, and are placed in a constant temperature and humidity chamber to maintain a moisture content of 20%-200%; S3 The rice straw long fibers prepared in S2 are subjected to directional twisting treatment by a manual twisting device, with a twist of 20 t / cm and a twist angle of 80°. The rice straw cellulose rope obtained after twisting has a diameter of 2-10 mm, a density of 1.4-1.5 g / cm³, a twist coefficient of 300-350, and a fiber orientation angle of 20°-25°; S4 The twisted rice straw fiber rope was impregnated with 10 wt% polyvinyl alcohol / soy protein isolate / chitosan / alkali lignin solution. The impregnation temperature was controlled to be 60 ℃, the time was 3 h, and then it was taken out and dried in a 60 ℃ oven for 8 h.

[0020] Fifth embodiment 5: S1 Rice straw softening process: Trioctyl methyl ammonium chloride salt-ammonium chloride low eutectic solvent and peroxy acid were used for softening and delignification treatment, with a solid-liquid ratio of 1:20. The pre-impregnation time was 60 min with trioctyl methyl ammonium chloride salt-ammonium chloride low eutectic solvent at room temperature of 5-40 °C, and then transferred to a high-temperature reactor. The treatment temperature was adjusted to 80 °C, the treatment time was 180 min, and the straw was washed with water to neutrality. Then, peroxy acid was used to assist delignification. The softened rice straw was washed with water to neutrality. The crystallinity, cellulose content of 75%-85%, hemicellulose content of 2%-5%, lignin content of 1%-6%, ash content of 1%-4%, wall thickness of 12-15 μm, wall layer gap of 3.0-4.5 μm, and wall layer porosity of 65%-70% were measured. S2. The rice straw softened in step S1 is treated with a wire rod coater, and is subjected to reciprocating rolling and separation processing along its radial direction, and rice straw long fibers with a diameter of 100-2000 μm and a length of 100-500 mm are separated according to the gap depth and the number of rolling times, and are placed in a constant temperature and humidity chamber to maintain a moisture content of 20%-200%; S3 The rice straw long fibers prepared in S2 are subjected to directional twisting treatment by a manual twisting device, with a twist of 20 t / cm and a twist angle of 80°. The rice straw cellulose rope obtained after twisting has a diameter of 2-10 mm, a density of 1.3-1.5 g / cm³, a twist coefficient of 330-360°, and a fiber orientation angle of 60°-80°; S4 The twisted rice straw fiber rope was impregnated with 10 wt% polyvinyl alcohol / soy protein isolate / chitosan / alkali lignin solution. The impregnation temperature was controlled to be 60 ℃, the time was 3 h, and then it was taken out and dried in a 60 ℃ oven for 8 h.

[0021] Sixth embodiment 6: S1 Rice straw softening process: Sodium hydroxide, sodium sulfite and peroxy acid were used for softening and delignification treatment, with a solid-liquid ratio of 1:20. The straw was pre-impregnated with sodium hydroxide solution at room temperature of 5-40 °C for 120 min, transferred to a high-temperature reactor, and the treatment temperature was adjusted to 80 °C for 60 min. After washing to neutrality, peracetic acid was used for full delignification treatment. The softened rice straw had a crystallinity of 45%-60%, a cellulose content of 90%-95%, a hemicellulose content of 1%-4%, a lignin content of 0%-2%, an ash content of 0-1%, a wall thickness of 10-12 μm, a wall interlayer gap of 2.5-4.5 μm, and a wall porosity of 70%-75%. S2. The rice straw softened in step S1 is treated with a wire rod coater, and is subjected to reciprocating rolling and separation processing along its radial direction, and rice straw long fibers with a diameter of 100-2000 μm and a length of 100-500 mm are separated according to the gap depth and the number of rolling times, and are placed in a constant temperature and humidity chamber to maintain a moisture content of 20%-200%; S3 The rice straw long fibers prepared in S2 are subjected to directional twisting treatment by a manual twisting device, with a twist of 10 t / cm and a twist angle of 50°. The rice straw cellulose rope obtained after twisting has a diameter of 1-6 mm, a density of 0.9-1.3 g / cm³, a twist coefficient of 330-360, and a fiber orientation angle of 30°-60°; S4 The twisted rice straw fiber rope was impregnated with 8 wt% polyvinyl alcohol / soy protein isolate / chitosan / alkali lignin solution. The impregnation temperature was controlled at 60 °C for 3 h, and then it was taken out and dried in an oven at 60 °C for 8 h.

[0022] Comparative Example 1: Original Rice Straw The untreated rice straw was measured to have a cellulose content of 30%~40%, a hemicellulose content of 20%~30%, a lignin content of 10%~20%, an ash content of 5%~15% (silicon content of 3%~12%), a porosity of 30%~40%, a wall thickness of 10~25 μm, a wall interlayer gap of 1.5~4 μm, a wall layer porosity of 40%~50%, and a crystallinity of 25%~40%. A single rice straw was used as a comparison.

[0023] Comparative Example 2: Directly twisting the original rice straw into rope S1 untreated rice straw, with a cellulose content of 30%-40%, a hemicellulose content of 20%-30%, a lignin content of 10%-20%, an ash content of 5%-15% (silicon content of 3%-12%), a porosity of 30%-40%, a wall thickness of 10-25 μm, a wall interlayer gap of 1.5-4 μm, a wall porosity of 40%-50%, and a crystallinity of 25%-40%; S3 The rice straw in S1 is subjected to directional twisting by a manual twisting device, with a twist of 20 t / cm and a twist angle of 60°. The rice straw cellulose rope obtained after twisting has a diameter of 4-10 mm, a density of 1.2-1.5 g / cm³, a twist coefficient of 260-300, and a fiber orientation angle of 60°-80°.

[0024] Comparative Example 3: Preparation of Rice Straw Fiber Rope by Natural Retting and Softening S1 uses rice straw as raw material and adopts natural retting method for softening treatment. The solid-liquid ratio is 1:10. It is retting at room temperature (5-40 ℃) for 10 days. The softened rice straw has a crystallinity of 20%-30%, a cellulose content of 30%-45%, a hemicellulose content of 10%-15%, a lignin content of 9%-18%, an ash content of 4-12%, a wall thickness of 12-14 μm, a wall gap of 2.0-3.0 μm, and a wall porosity of 55%-65%. S2. The rice straw in step S1 is treated with a wire rod coater, and is subjected to radial reciprocating rolling and separation treatment to obtain rice straw long fibers with a diameter of 100-2000 μm and a length of 100-500 mm according to the gap depth and the number of rolling times, and is placed in a constant temperature and humidity chamber to maintain a moisture content of 20%-200%; S3 The rice straw long fibers prepared in S2 are subjected to directional twisting treatment by a manual twisting device, with a twist of 20 t / cm and a twist angle of 60°. The rice straw cellulose rope obtained after twisting has a diameter of 4-10 mm, a density of 1.2-1.5 g / cm³, a twist coefficient of 260-300, and a fiber orientation angle of 60°-80°; S4 The twisted rice straw fiber rope was impregnated with 1 wt% polyvinyl alcohol / soy protein isolate / chitosan / alkali lignin solution. The impregnation temperature was controlled at 40 °C for 6 h, and then it was taken out and dried in a 40 °C oven for 12 h.

[0025] Test Example 1 The original rice straw, hot and water-boiling rice straw (first embodiment), partially delignified rice straw (third embodiment), and fully delignified rice straw (sixth embodiment) in the present invention were characterized in kind and microscopic morphology. Figure 2 .

[0026] The test method is as follows: Scanning electron microscope (SEM) was used to observe the microscopic morphology of rice straw before and after treatment.

[0027] like Figure 2 As shown, Figure a is a real picture of the original rice straw, and Figure e is a microscopic morphology of Figure a. Figure b is a real picture of hydrothermal rice straw, and Figure f is a microscopic morphology of Figure b, that is, the picture after the first embodiment is softened by subcritical hydrothermal treatment. Figure c is a real picture of partially delignified rice straw, and Figure g is a microscopic morphology of Figure c, that is, the picture after the third embodiment is softened. Figure d is a real picture of fully delignified rice straw, and Figure g is a microscopic morphology of Figure d, that is, the picture after the sixth embodiment is softened. Comparing Figures a to d, it can be seen that after softening treatment, the color of the rice straw changes from dark to light to white, which is due to the gradual reduction of the lignin component in the rice straw. Comparing Figures e to g, it can be seen that with the removal of the lignin component in the rice straw, the surface of the rice straw becomes smoother and the fibrillation increases.

[0028] Test Example 2 The rice straws prepared in Examples 1-6 of the present invention and Comparative Example 3 were tested for cellulose, hemicellulose, lignin content and crystallinity. The results are shown in Tables 1, 2 and Figure 4 .

[0029] The test method is as follows: the contents of cellulose, hemicellulose and lignin are determined by the NREL method; the crystallinity of the rice straw before and after treatment is calculated by measuring the XRD diffraction peak intensity of the rice straw.

[0030] Table 1 Cellulose, hemicellulose, lignin content and crystallinity of original rice straw and straw obtained after softening treatment in the examples and comparative examples; Sample name Cellulose Hemicellulose Lignin Crystallinity Raw rice straw 30%~40% 20%~30% 10%~20% 25%~40% First Example: Rice straw after softening 55%~60% 10%~15% 10%~18% 28%~40% Second Example: Rice straw after softening 55%~60% 8%~12% 10%~13% 30%~45% Example 3: Rice straw after softening 55%~65% 2%~5% 5%~10% 40%~48% Fourth Example: Rice straw after softening 60%~65% 5%~8% 4%~8% 45%~50% Fifth Example: Rice straw after softening 75%~85% 2%~5% 1%~6% 48%~55% Sixth Example: Rice straw after softening 90%~95% 1%~4% 0%~2% 45%~60% Comparative Example 3: Rice straw after softening 30%~45% 10%~15% 9%~18% 20%~30% It can be seen from Table 1 that after the softening treatment of Examples 1-6, the hemicellulose and lignin in the rice straw were removed to varying degrees, and the crystallinity of the rice straw increased with the increase of the cellulose content, indicating that the chemical composition and microstructure of the rice straw can be regulated by the softening process, and the mechanical properties of the rice straw can be changed; while in Comparative Example 3, during the natural retting process, part of the cellulose in the rice straw was degraded by the action of microorganisms, and the crystallinity was reduced. Since the molecular chains in the crystalline region are highly ordered and provide higher tensile strength through strong intermolecular forces (such as van der Waals forces and hydrogen bonds), the crystal structure can effectively withstand and disperse external stress, and the fibers with higher crystallinity have better mechanical tensile strength. Figure 4 It can be seen that with the removal of hemicellulose and lignin components in rice straw, the peak intensity of rice straw near 15.8 and 22.3 becomes higher, indicating that different softening treatments can adjust the chemical composition and crystallinity of rice straw.

[0031] Test Example 3 The original rice straw, hot and water-boiling rice straw (first embodiment), partially delignified rice straw (third embodiment), and fully delignified rice straw (sixth embodiment) of the present invention were characterized by Fourier transform infrared spectroscopy. The results are shown in FIG. Figure 5 .

[0032] The test method is as follows: The potassium bromide tablet method is used to measure the 500~4000 cm -1 Absorption spectrum at .

[0033] like Figure 5 As shown, the wave number is 3423 cm -1 and 2916 cm -1 The peaks at 1733 cm are generated by CH in hydroxyl, methyl and methylene respectively. The intensity of the characteristic peaks here is enhanced after different softening treatments, indicating that after softening treatment, the structure of rice straw is destroyed and more cellulose is exposed; -1 and 1625 cm -1 The absorption peak at 1515 cm -1 The typical absorption peak at mainly comes from the stretching vibration of conjugated carbon groups in lignin. As the lignin content decreases, the intensity decreases. For fully delignified rice straw, the peak disappears.

[0034] Test Example 4 The mechanical properties of the rice straw fiber ropes prepared in Examples 1-6 of the present invention and Comparative Examples 1-3 were tested. The results are shown in Tables 2 and 3.

[0035] The test method is as follows: referring to the national standards GB / T 14344-2022 and GB / T 1447-2005, the tensile properties of rice straw fiber ropes were tested on a desktop electronic universal material testing machine.

[0036] Table 2 Tensile performance test of the nanofiber flexible membrane and spiral long fiber in the comparative example; sample Preparation process Crystallinity (%) Tensile strength(MPa) Elongation at break (%) Comparative Example 1 Raw rice straw 30 20~30 5~10 Comparative Example 2 Original rice straw twisted fiber rope 30 45~60 3~8 Comparative Example 3 Naturally retting and softening rice straw twisted fiber rope 28 70~80 10~15 It can be seen from Table 2 that in Comparative Example 1, the tensile strength of the original untwisted rice straw is 20-30 MPa, and the elongation at break is 5%-10%. After twisting treatment (Comparative Example 2), the tensile strength is increased to 45-60 MPa, and the elongation at break is reduced to 3%-8%, indicating that the twisting treatment forms a spiral structure in the rice straw, which can improve the mechanical strength of the rice straw; while in Comparative Example 3, the internal chemical composition and microstructure of the rice straw are changed by natural retting and softening treatment. Although the crystallinity is slightly reduced, the tensile strength of the fiber rope is increased to 70-80 MPa after twisting. This is because the internal structure of the rice straw changes after softening treatment, and the flexibility and plasticity are enhanced, which changes the stress transfer of the rice straw and increases its mechanical properties.

[0037] Table 3 Tensile performance test of rice straw fiber rope in the embodiment; sample Preparation process Crystallinity (%) Tensile strength(MPa) Elongation at break (%) First embodiment Subcritical hydrothermal softening of rice straw long fibers (160℃, 90 min) 30 30~60 30~100 Second embodiment Subcritical hydrothermal softening of rice straw long fibers (200℃, 30 min) 35 50~70 50~200 Third embodiment Formic acid / methanol softening of rice straw long fibers (100℃, 40 min) 42 60~100 80~300 Fourth embodiment Choline chloride-ethylenediamine softening of rice straw long fibers (120℃, 60 min) 48 65~120 80~310 Fifth embodiment Trioctylmethylammonium chloride-ammonium chloride assisted peroxyacid softening of rice straw long fibers (80℃, 180 min) 53 60~140 50~310 Sixth embodiment Sodium hydroxide-sodium sulfite assisted peroxyacid softening of rice straw long fibers (80℃, 60 min) 58 80~240 60~330 As shown in Table 3, the rice straw was processed by various processes, and the chemical composition and crystallinity of the straw were regulated and twisted to improve the fiber bonding strength, so as to obtain a spiral rice straw baling rope with high strength and toughness.

[0038] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a rice straw fiber rope, characterized in that: The following steps are involved: S1. Rice straw softening process: rice straw is treated with a softening solvent to regulate the chemical composition and physical structure of the cell wall of rice straw; the softening solvent comprises one or more of water, organic solvent, low eutectic solvent and Lewis base, the solid-liquid mass ratio of rice straw to softening solvent is 1:5~1:100, the pre-impregnation time is 5~500min at room temperature (5~40℃), and then the mixture is transferred to a high-temperature reactor, the treatment temperature is adjusted to 60~300℃, the pressure value is adjusted to 0.02~8.6 MPa, and the treatment time is 5~300 min, and after natural cooling, wash with water until neutral to obtain softened rice straw; the water includes tap water, distilled water or deionized water; the organic solvent includes one or more combinations of methanol, ethanol, acetone, γ-valerolactone, formic acid, acetic acid, p-toluenesulfonic acid, and oxalic acid; the low eutectic solvent includes one or more combinations of choline chloride system and trioctylmethylammonium chloride salt system; the Lewis base includes one or more combinations of ammonia water, sodium hydroxide, potassium hydroxide, aluminum chloride hexahydrate, and sodium carbonate; S2. Separation and preparation of long fibers from rice straw: The softened rice straw obtained in S1 was subjected to reciprocating rolling and splitting treatment along the radial direction of the straw using a wire rod coater to separate the long fibers from the rice straw, and the long fibers were placed in a constant temperature and humidity chamber to maintain a moisture content of 20% to 200%; S3. Directed spiral structure twisting process: The rice straw long fibers separated in S2 are subjected to directional twisting by a twisting device to obtain a rice straw long fiber rope with a spiral structure, high strength and high tenacity; the twisting process is set to a twist of 5-20 t / cm, a twist angle of 10°-80°, and a twist coefficient of 250-400. The diameter of the twisted rice straw fiber rope is 0.5-30 mm, the density is 0.9-1.5 g / cm³, the internal fiber orientation angle is 5°-88°, the tensile strength is 50-600 MPa, and the tensile fracture deformation rate is 10%-100%; S4. Post-treatment and curing: The rice straw fiber rope is impregnated with an impregnation solution including polyvinyl alcohol, soy protein isolate, chitosan, and alkali lignin polymer solution. The concentration of the polymer in deionized water is controlled at 0.1wt%~10wt%, the impregnation temperature is controlled at 40~60℃, and the impregnation time is controlled at 1~6h to ensure that the rice straw fiber rope is in full contact with the polymer. After the impregnation treatment, the fiber rope is taken out and naturally air-dried at 20~40℃ or heat-dried in an oven at 40~60℃ for 2~48h.

2. The method for preparing the rice straw fiber rope according to claim 1, characterized in that: In step S1, it specifically includes: using subcritical hydrothermal to soften, using water as the softening solvent, the solid-liquid mass ratio of rice straw to the softening solvent is 1:5, pre-impregnation time is 500 min at room temperature (5~40 ℃), transferring to a high-temperature reactor, adjusting the treatment temperature to 160 ℃, and the treatment time is 90 min. It is measured that the softened rice straw has a crystallinity of 28%~40%, a cellulose content of 55%~60%, a hemicellulose content of 10%~15%, a lignin content of 10%~18%, an ash content of 4%~5%, a wall thickness of 15~20 μm, a wall layer gap of 1.5~3.0 μm, and a wall layer porosity of 55%~65%.

3. The method for preparing the rice straw fiber rope according to claim 1, characterized in that: In step S1, it specifically includes: using subcritical hydrothermal to soften the straw with a solid-liquid ratio of 1:10, pre-impregnating for 300 minutes at room temperature (5-40 °C), transferring to a high-temperature reactor, adjusting the treatment temperature to 200 °C, and treating for 30 minutes. The softened rice straw is measured to have a crystallinity of 30%-45%, a cellulose content of 55%-60%, a hemicellulose content of 8%-12%, a lignin content of 10%-13%, an ash content of 5%-7%, a wall thickness of 13-18 μm, a wall layer gap of 2.1-3.5 μm, and a wall layer porosity of 60%-65%.

4. The method for preparing the rice straw fiber rope according to claim 1, characterized in that: In step S1, it specifically includes: softening treatment with formic acid-methanol system, solid-liquid ratio of 1:10, pre-impregnation time of 60 minutes at room temperature (5-40 ° C), transferring to a high-temperature reactor, adjusting the treatment temperature to 100 ° C, treatment time of 40 minutes, washing to neutrality, and measuring the softened rice straw has a crystallinity of 40%-48%, a cellulose content of 55%-65%, a hemicellulose content of 2%-5%, a lignin content of 5%-10%, an ash content of 4%-5%, a wall thickness of 12-15 μm, a wall layer gap of 2.5-3.8 μm, and a wall layer porosity of 60%-65%.

5. The method for preparing the rice straw fiber rope according to claim 1, characterized in that: In step S1, it specifically includes: softening treatment with choline chloride-ethylenediamine low eutectic solvent, solid-liquid ratio of 1:30, pre-impregnation time at room temperature (5-40 ° C) for 60 min, transferring to a high-temperature reactor, adjusting the treatment temperature to 120 ° C, treatment time 60 min, washing to neutrality, and measuring the softened rice straw has a crystallinity of 45%-50%, a cellulose content of 60%-65%, a hemicellulose content of 5%-8%, a lignin content of 4%-8%, an ash content of 2%-4%, a wall thickness of 15-18 μm, a wall layer gap of 2.0-3.5 μm, and a wall layer porosity of 55%-60%.

6. The method for preparing the rice straw fiber rope according to claim 1, characterized in that: In step S1, it specifically includes: using trioctyl methyl ammonium chloride salt-ammonium chloride low eutectic solvent and peroxy acid for softening and delignification treatment, the solid-liquid ratio is 1:20, pre-impregnating with trioctyl methyl ammonium chloride salt-ammonium chloride low eutectic solvent for 60 minutes at room temperature (5-40 ° C), transferring to a high-temperature reactor, adjusting the treatment temperature to 80 ° C, the treatment time is 180 min, washing with water to neutrality, and then using peroxy acid to assist delignification, washing with water to neutrality. The softened rice straw is measured to have a crystallinity of 45%-55%, a cellulose content of 75%-85%, a hemicellulose content of 2%-5%, a lignin content of 1%-6%, an ash content of 1%-4%, a wall thickness of 12-15 μm, a wall layer gap of 3.0-4.5 μm, and a wall layer porosity of 65%-70%.

7. The method for preparing a rice straw fiber rope according to claim 1, characterized in that: In step S1, it specifically includes: using sodium hydroxide, sodium sulfite and peroxy acid for softening and delignification treatment, with a solid-liquid ratio of 1:20, pre-impregnating with sodium hydroxide solution for 120 min at room temperature (5-40 ° C), transferring to a high-temperature reactor, adjusting the treatment temperature to 80 ° C, the treatment time is 60 min, washing with water to neutrality, and then using peracetic acid for full delignification treatment. After washing with water to neutrality, it is measured that the softened rice straw has a crystallinity of 45%-60%, a cellulose content of 90%-95%, a hemicellulose content of 1%-4%, a lignin content of 0%-2%, an ash content of 0-1%, a wall thickness of 10-12 μm, a wall layer gap of 2.5-4.5 μm, and a wall layer porosity of 70%-75%.

8. The method for preparing the rice straw fiber rope according to claim 1, characterized in that: In the long fiber separation and preparation step of S2, the fiber separation device used is a wire rod coater, which is made of metal such as marble, stainless steel, copper or alloy, with a length of 200~800 mm, a wire rod diameter of 5.6~9.52 mm, a coil diameter of 9.72~14.34 mm, and a coil gap of 100~1000 μm. The separated rice straw long fibers have a diameter of 50~800 μm and a length of 100~500 mm.

9. The method for preparing a rice straw fiber rope according to claim 1, characterized in that: The rice straw long fibers obtained by the silk splitting in step S3 are subjected to directional twisting by a manual or mechanical twisting device, wherein the twist degree is 5-20 t / cm, the twist angle is 10°-80°, the twist coefficient is 250-400, the diameter of the twisted fibers is 0.05-30 mm, the length is 0.01-100 m, the density is 0.9-1.5 g / cm³, and the orientation angle of the nanofibers inside the fibers is 5°-88°.

10. The method for preparing a rice straw fiber rope according to claim 1, characterized in that: In step S4, the twisted rice straw fiber rope is cured by using a high molecular polymer, which specifically includes: setting the concentration of the impregnation liquid to 0.1wt%~10wt%, the impregnation temperature to 40~60℃, and the impregnation time to 1~6 hours to ensure that the rice straw fiber rope is in full contact with the high molecular polymer, and the impregnated rice straw fiber rope is cured by natural air drying or oven heat drying.

Citation Information

Patent Citations

  • Degradable straw fiber

    CN102561095A

  • Novel dihydrogen bond deep-eutectic solvent and method for pretreating rice straws through combination of solvent and sodium carbonate

    CN107760739A

  • Preparation method of bio-mechanical pulp treated by bio-enzyme

    CN114921992A

  • Preparation method of high-length-diameter-ratio straw fibers and application of high-length-diameter-ratio straw fibers in needling forming straw blanket

    CN115537938A

  • Bamboo fiber rope manufacturing method, bamboo fiber bundle manufacturing method, and bamboo fiber rope

    JP2009154387A